Nigeria's educational process and ethical re-orientation (2009)
The need for value and ethical re-orientation of Nigerians have become very essential especially at such a time when the country has attained fifty years of independence with no concrete achievements besides those of the sixties. Concerns have been raised as to the veracity of education in inculcating appropriate social and moral values in leakers for the development of the country going by their attitudes and actions. The western education has been acclaimed to be responsible for the influx of certain social values that had bedeviled the sanctity of the African and Nigerian society. Africans are known for the principle of communalism among others unlike the individuality of the western 'culture. The need to give greater considerations to our indigenous values is highlighted in this article. It was realised that learners should be made to understand moral concepts through the lessons learnt in their classrooms to further entrench these African values. Similarly, social values of tolerance and sympathy need to be emphasised in order to re-orientate Nigerians for the envisaged growth